ANALISIS PENGARUH KOMITMEN AFEKTIF, KOMITMEN BERKELANJUTAN DAN KOMITMEN NORMATIF TERHADAP KINERJA KARYAWAN PADA PT RADIO NEBULA NADA DI KOTA PALU - DWI PATHAN, RAZIYAM (Fakultas Ekonomi Universitas Tadulako, 2016)
The purpose of this study is to determine and analyze the influence of affective commitment variable (X1), continuous Commitment (X2), and Normative commitment (X3) at PT. Radio Nebula Nada in Palu City. Hypothesis test used has significance level of ? =0.05 and for the reliability test using cronbach alpha coefficient values with the limit value coefficient of ?=0.60. The results of multiple linear regression analysis show that the variables of affective commitment (X1) and the continous commitment (X2), normative commitment (X3) simultaneously have positive and significant influence on the performance of employees at PT. Radio Nebula Nada in Palu with the adjusted R- square of 32.6%. Partially, with standard ? = 0.05, X1, X2, and X3 partially have significant influence on Y with sig. value of 0.016, 0.086, and 0.015, respectively. The results show that correlation coefficient of 0.627, means that affective commitment, continuous commitment, and normative commitment have strong relationship with the employee's performance of 62.7%.